Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan Pada PT. Sri Aneka Karyatama Palembang - Yussi Rapareni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine how the influence of leadership style on employee morale, the influence of the work environment on employee morale, and the influence of leadership style and work environment on employee morale of PT. Sri Aneka Karyatama Palembang. The research sample is all permanent employees of PT. Sri Aneka Karyatama Palembang. The variables of this study are leadership style (X₁ ), work environment (X₂ ), and employee morale (Y). The data used are primary data and secondary data, data collection techniques are questionnaires and documents. The data is analyzed using quantitative analysis and the analysis tool uses SPSS Version 16. The results shows that leadership style variables (X₁ ) and work environment (X₂ ) significantly affected work morale (Y). The magnitude of the effect of independent variables with the dependent variable in this study is indicated by the value of R Square of 45% and Adj. R Square by 41%. Other influences beyond the variables studied or called error (e) are of 55%. Thus, it can be concluded that there is a significant and positive influence between leadership style and work environment on employee morale at PT. Sri Aneka Karyatama Palembang.